Perfil de metilação do DNA no gene ADRB3 em indivíduos adultos por índice de massa corporal e relação com perfil lipídico, estresse oxidativo e consumo alimentar: um estudo de base populacional - Oliveira, Yohanna de (2018)
Researchers have highlighted the role of DNA methylation as a potential epigenetic mechanism related to several candidate genes for the development of obesity and changes in lipid metabolism. Therefore, in view of the relationship between gene and obesity, the aim of this study was to evaluate DNA methylation levels in the ADRB3 gene by body mass index (BMI) and to correlate with lipid profile, oxidative stress and food intake. This is a cross-sectional population-based study, with 262 adults aged 20-59 years, of both sexes, representative of the eastern and western zones of the city of João Pessoa/PB. The questionnaires related to the demographic, socioeconomic, epidemiological and lifestyle variables, as well as the nutritional assessment were applied in the households. For the biochemical analyzes, the serum concentrations of homocysteine, alpha-1-acid glycoprotein, lipid profile, folic acid, vitamin B12, malondialdehyde (MDA) and total antioxidant capacity (TAC) were analyzed. For the analysis of DNA methylation levels in the ADRB3 gene, the PCR real time method was used. The relationships between the study variables were performed using analysis of variance (ANOVA) and multiple regression models. All results were obtained using software version 3.3.2. From the stratification of BMI categories, there was a mean difference in the values of age, waist-to-height ratio (WHtR), waist-to-hip ratio (WHR), waist circumference (WC), triglycerides and trans fat consumption, which occurred more in the categories "eutrophy" and "obesity". From the multiple regression analysis in the eutrophic group, negative relationship was observed between the methylation levels of the ADRB3 gene with sérum folic acid levels, as well as with the gender-independent BMI. However, it was not observed a relationship between lipid profile, oxidative stress and food intake in the individuals distributed in the three categories of BMI. The absence of a relationship between methylation levels of the ADRB3 gene in overweight and mild and moderate obesity can be explained by the insufficient amount of body fat to initiate inflammatory processes and oxidative stress with a direct impact on methylation levels.